The case for integrated health and community literacy to achieve transformational community engagement and improved health outcomes: an inclusive approach to addressing rural and remote health inequities and community healthcare expectations. (2nd December 2020) - Jones, Debra; Lyle, David; McAllister, Lindy; Randall, Sue; Dyson, Robert; White, Danielle; Smith, Aimee; Hampton, Denise; Goldsworthy, Mariah; Rowe, Alesha
Abstract: Context: Despite the substantial investment by Australian health authorities to improve the health of rural and remote communities, rural residents continue to experience health care access challenges and poorer health outcomes. Health literacy and community engagement are both considered critical in addressing these health inequities. However, the current focus on health literacy can place undue burdens of responsibility for healthcare on individuals from disadvantaged communities whilst not taking due account of broader community needs and healthcare expectations. This can also marginalize the influence of community solidarity and mobilization in effecting healthcare improvements. Objective: The objective is to present a conceptual framework that describes community literacy, its alignment with health literacy, and its relationship to concepts of community engaged healthcare. Findings: Community literacy aims to integrate community knowledge, skills and resources into the design, delivery and adaptation of healthcare policies, and services at regional and local levels, with the provision of primary, secondary, and tertiary healthcare that aligns to individual community contexts. A set of principles is proposed to support the development of community literacy. Three levels of community literacy education for health personnel have been described that align with those applied to health literacy for consumers. It is proposed that community literacy education can facilitate transformational community engagement. Skills acquired by health personnel from senior executives to frontline clinical staff, can also lead to enhanced opportunities to promote health literacy for individuals. Conclusions: The integration of health and community literacy provides a holistic framework that has the potential to effectively respond to the diversity of rural and remote Australian communities and their healthcare needs and expectations. Further research is required to develop, validate, and evaluate the three levels of community literacy education and alignment to health policy, prior to promoting its uptake more widely.